Risk factors of acute heart failure after the first episode of acute coronary syndrome - Tariq, Fatima; Rehman, Qavi Ur; Khan, Abdullah; Asif, Haiqa; Asif, Abdul Eizad; Shamsher, Muhammad Faisal; Ain, Qurat Ul; Munir, Ahad; Muneer, Fahad; Ahmed, Ali; Khan, Tayyab Mumtaz (International Journal Of Community Medicine And Public Health, 2024)
Background: Factors that speed up the development of acute heart failure (AHF) after acute coronary syndrome (ACS), are understudied in developing country like Pakistan. Therefore, this study was aimed to determine the risk factor of heart failure (HF) among the post-ACS patients. Methods: This descriptive cross-sectional study was performed at Benazir Bhutto Hospital (BBH), Rawalpindi, Pakistan. 78 patients who were admitted with HF cardiology unit of BBH after ACS from March 2023 to April 2024 were enrolled in the study. An established inclusion and exclusion criteria along with consecutive sampling technique were used for patients’ recruitment. A self-structured proforma was applied to gather data. Data analysis was done in the statistical package for the social sciences (SPSS) version 25.0. Results: HF was more prevalent among those post-acute coronary syndrome patients who had an age group with 40 years or above (69.23%), male gender (62.82%), anterior wall myocardial infarction (38.46%), reduced ejection fraction (67.90%), left anterior descending artery pathology (17.95%), absence of myocardial revascularization procedure (46.15%), diabetes mellitus (52.56%), hypertension (78.20%), anemia (53.85%), hyperlipidemia (75.64%), and who had history of smoking (51.28%). A significant number of patients also had chronic kidney disease (23.10%). Conclusions: Factors such as an age group with 40 years or above, male gender, anterior wall myocardial infarction, reduced ejection fraction, left anterior descending artery pathology, absence of myocardial revascularization procedure, diabetes mellitus, hypertension, anemia, hyperlipidemia, and history of smoking, all accelerate the development of HF among post-ACS patients.